An Overall Comprehension of Anti‐Aromatic Porphyrinoids Using 3D‐Graphical Chemical Shielding Description. Issue 5 (3rd March 2020) - Qi, Dongdong; Jiang, Jianzhuang
Abstract: A systematic investigation to rank the anti‐aromatic porphyrinoids is performed. Based on density functional theory calculations, four rules are summarized to obtain the highest anti‐aromatic porphyrinoids: 1) the replacement from meso‐C to meso‐(─C≡C─), 2) the replacement from pyrrole unit to inner‐N to inner‐O, 3) the replacement from two opposite meso‐C/N atoms to two pyrrole units, and 4) the replacement from one pyrrole ring to a carbonyl benzene ring. It is worth noting that the long chain with alternating single/double bonds is not beneficial or harmful to the anti‐aromaticity. Abstract : Two advanced aromaticity/anti‐aromaticity simulating methods, 3D nuclear independent chemical shielding (3D‐NICS) and the integral of deshielded area in ring (IDR), are used to systematically investigate the aromaticity/anti‐aromaticity of porphyrinoids and quantitatively rank their anti‐aromaticity. In this anti‐aromatic rank, the oxygen‐confusing porphyrinoid is the champion.